A Five-Year report on the conception and establishment of the MSc Radiation Biology at the Technical University of Munich. (1st February 2021) - Kessel, Carmen; Atkinson, Michael J.; Schmid, Thomas E.; Trott, Klaus; Wilkens, Jan J.; Anastasov, Natasa; Rosemann, Michael; Azimzadeh, Omid; Tapio, Soile; Moertl, Simone; Kulka, Ulrike M.; Abend, Michael; et al.
Abstract: Purpose: The MSc Radiation Biology course is a highly interdisciplinary degree program placing radiation biology at the interface between biology, medicine, and physics, as well as their associated technologies. The goal was to establish an internationally acknowledged program with diverse and heterogeneous student cohorts, who benefit from each other academically as well as culturally. We have completed a Five-Year evaluation of the program to assess our qualification profile and the further direction we want to take. Materials and methods: We evaluated the student cohort's data from the last 5 years regarding gender, age, and nationality as well as the highest degree before applying and career path after graduation. Results: Data shows a great diversity regarding nationalty as well as undergraduate background. Cohort sizes could be increased and future prospects mainly aimed to a PhD. Measures after regular quality meetings and students' feedback led to improving the curriculum and workload, teacher's training, and changes to examination regulations. Conclusions: After 5 years, statistics show that our expectations have been met exceedingly. All graduates had excellent career opportunities reflecting the necessity of this MSc and its topics. We are continuously working on improving the program and adapting the curriculum to the requirements in radiation sciences. The future vision includes an expansion of the program as well as undergraduate education opportunities in this field.